A mild and efficient procedure for alkenols oxyselenocyclization by using ionic liquids - Kostic, Marina; Verdia, Pedro; Fernandez-Stefanuto, Veronica; Puchta, Ralph; Tojo, Emilia (Journal of Physical Organic Chemistry, 2019)
A mild and efficient procedure for the oxyselenocyclization of unsaturated alcohols by treatment with phenylselenyl chloride using ionic liquids as solvents/catalyzers has been developed. The reaction proceeds instantaneously under mild conditions with absolute regioselectivity, using primary, secondary, tertiary, and aromatic alcohols, as well as monosubstituted, disubstituted, and trisubstituted alkenols. This procedure provides a new method for the synthesis of substituted tetrahydrofurans and tetrahydropyrans ethers, the precursors of many biologically active metabolites, avoiding the use of toxic and corrosive catalysts. There are no previous reports of selenium-mediated cyclofuncionalization reactions in ionic liquids. Taking into the account the good results obtained with [MMIM][MSO 4 ], its ease preparation, low viscosity, low price, and its capacity to be recovered and reused, it was selected as the solvent/catalyzer. Quantum-chemical calculations (MP2(fc)/6-311 + G**//B3LYP/6-311 + G**) has shown that the intramolecular cyclization is promoted by the hydrogen bond formed between the ionic liquid anion and the hydroxyl group of the alkenol.
CRIS-Team Scopus Importer:2019-05-02
Keywords: catalysis; ionic liquids; oxyselenocyclization; quantum-chemical calculations; sustainable chemistry